2012
DOI: 10.1103/physrevb.85.064118
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the high-pressure behavior of superhard tungsten tetraboride

Abstract: Abstract:In this work, we examine the high pressure behavior of superhard material candidate WB 4 using high-pressure synchrotron X-ray diffraction in a diamond anvil cell up to 58.4 GPa. The zero-pressure bulk modulus, K 0 , obtained from fitting the pressure-volume data using the second-order Birch-Murnaghan equation of state is 326 ± 3 GPa. A reversible, discontinuous change in slope in the c/a ratio is further observed at ~42 GPa, suggesting that lattice softening occurs in the c direction above this press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
97
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(128 citation statements)
references
References 65 publications
25
97
5
Order By: Relevance
“…If we set Φ = 0 (so σ zz = 0) in the calculation, it is equivalent to require that all the five stress components (except σ xz ) become negligible during the structural relaxation, which is the relaxation procedure used in the previous calculations of pure ideal shear stresses [28][29][30][31][32][33][34][35][36][37][38][41][42][43][44][45][46][47][48] that neglect the effects of the normal compressive pressure and geometry (indenter angles) of the indenter. Our test calculations for the lattice vectors of the equilibrium structure of Re, Re 3 N, Re 2 N, Re 2 C, Re 2 B and ReB 2 , their bulk moduli and Poisson's ratios are given in Table I, which agree well with the previous calculation results 19,[21][22][23][24]54,55 . The bulk moduli are obtained by fitting the energy-volume curves near the equilibrium structures to the Murnaghan equation, and the Poisson's ratios are evaluated from the calculated elastic constants.…”
Section: II Computation Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…If we set Φ = 0 (so σ zz = 0) in the calculation, it is equivalent to require that all the five stress components (except σ xz ) become negligible during the structural relaxation, which is the relaxation procedure used in the previous calculations of pure ideal shear stresses [28][29][30][31][32][33][34][35][36][37][38][41][42][43][44][45][46][47][48] that neglect the effects of the normal compressive pressure and geometry (indenter angles) of the indenter. Our test calculations for the lattice vectors of the equilibrium structure of Re, Re 3 N, Re 2 N, Re 2 C, Re 2 B and ReB 2 , their bulk moduli and Poisson's ratios are given in Table I, which agree well with the previous calculation results 19,[21][22][23][24]54,55 . The bulk moduli are obtained by fitting the energy-volume curves near the equilibrium structures to the Murnaghan equation, and the Poisson's ratios are evaluated from the calculated elastic constants.…”
Section: II Computation Methodssupporting
confidence: 79%
“…It is difficult to compress their volumes by hydrostatic pressure, which results in their high bulk moduli. However, in indentation hardness tests the uniaxial normal compressive pressure beneath the indenter can cause a large lateral volume expansion of the valence electrons in these structures as indicated by their large Poisson's ratios [19][20][21][22][23][24] . We examine how this lateral expansion affects the mechanical strength under indentation of these compounds with different chemical elements and compositions.…”
mentioning
confidence: 99%
“…The more striking fact is that none of them agrees with the theoretically derived pressure-dependent c/a ratio [31] of hP 16-WB 3 . Therefore, this tungsten boride still needs further clarification.Within this context, by combining first-principles calculations [32,33] (unless otherwise mentioned, all calculations have been performed with the Perdew-BurkeErnzerh generalized gradient approximation (GGA-type PBE) [34]), variable-composition evolutionary algorithm search as implemented recently in USPEX [35,36] and the aberration-corrected images of high resolution transmission electron microscopy (Ac-HRTEM) (method details refers to Supporting information), we have confirmed the existence of WB 3+x (x < 0.5) (including the stoichiometric hP 16-WB 3 ) and denied the formation of the extensively debated boride of hP 20-WB 4 [17,27,28]. The previously experimentally attributed WB 4 is indeed WB 3+x .…”
mentioning
confidence: 60%
“…First-principles calculations suggested that hP6-WB 2 was energetically more stable than the experimentally reported hP3-WB 2 [12] and could have the high hardness with a value of 43.8-47.4 GPa [13,14]. It was once accepted that the claimed hP20-WB 4 [15] was an inexpensive superhard material (Vickers hardness 43.3-46.2 GPa under the load of 0.49 N) [16][17][18][19]. However, this long-assumed hP20-WB 4 has recently identified as hP16-WB 3 from the thermodynamic stability [20], mechanical properties [21] and XRD spectra comparisons [22,23].…”
mentioning
confidence: 97%